Schwann Cell Autophagy and Necrosis as Mechanisms of Cell Death by Acanthamoeba - Ismael Castelan-Ramírez; Lizbeth Salazar-Villatoro; Bibiana Chávez-Munguía; Citlaltepetl Salinas-Lara; Carlos Sánchez-Garibay; Catalina Flores-Maldonado; Dolores Hernández-Martínez; Verónica Anaya-Martínez; María Rosa Ávila-Costa; Adolfo René Méndez-Cruz; Maritza Omaña-Molina (Pathogens, 2020)
Amoebae of the genus Acanthamoeba are etiological agents of granulomatous amoebic encephalitis (GAE). Recently, through an in vivo GAE model, Acanthamoeba trophozoites were immunolocalized in contact with the peripheral nervous system (PNS) cells—Schwann cells (SC). In this study, we analyzed in greater detail the in vitro early morphological events (1, 2, 3, and 4 h) during the interaction of A. culbertsoni trophozoites (ATCC 30171) with SC from Rattus norvegicus (ATCC CRL-2941). Samples were processed for scanning and transmission electron microscopy as well as confocal microscopy. After 1 h of interaction, amoebae were observed to be adhered to the SC cultures, emitting sucker-like structures associated with micro-phagocytic channels. In addition, evidence of necrosis was identified since edematous organelles as well as multivesicular and multilamellar bodies characteristics of autophagy were detected. At 2 h, trophozoites migrated beneath the SC culture in which necrosis and autophagy persisted. By 3 and 4 h, extensive lytic zones were observed. SC necrosis was confirmed by confocal microscopy. We reported for the first time the induction of autophagic and necrotic processes in PNS cells, associated in part with the contact-dependent pathogenic mechanisms of A. culbertsoni trophozoites.